Anglo Sikh Heritage Trail : Preserving the Past, Inspiring the Future (2004)
[Dt.:]Anglo Sikh Heritage Trail ist ein von der 'Heritage Lottery Fund' und 'English Heritage' unterstütztes Projekt, welches 2004 startete. Es verfolgt die Absicht, das Anglo-Sikh-Erbe mit Hilfe von verschiedenen Initiativen zu beleuchten und zu fördern. Unter diesen gehören Ausstellungen, Lesungen und weitere Projekte. - [Engl.:]Anglo Sikh Heritage Trail is a cultural project supported by 'Heritage Lottery Fund' and 'English Heritage', starting in 2004. It follows the ambition to highlight and promote the Anglo-Sikh heritage through different initiatives as exhibitions, lectures and other projects.